Studi Problem Based Learning : Suatu Inovasi Pendidikan Berbasis Pemecahan Masalah - Idil Idil; Dedi Harianto; Muh Rezky Septiawan; Salma Rumaday (PT. Citra Media Publishing, 2025)
Problem Based Learning (PBL) is a learning model that takes and uses examples from real life. With this method, learners are trained to solve a problem through discussions, problem exercises, or scientific activities. This research was conducted to see the role of Problem Based Learning in developing students' critical thinking skills. In this research, a literature study was conducted by collecting explanations from various sources such as books and articles that discuss PBL. The researcher's findings revealed the success of the Problem Based Learning model in improving students' critical thinking skills. Problem Based Learning trains learners to think in real terms, and consider various views in the decision-making process. This problem-solving-oriented approach not only deepens the learning experience, but also makes it more relevant to everyday life.